Ultraviolet Radiation and Basal Cell Carcinoma: An Environmental Perspective - Teng, Yan; Yu, Yong; Li, Sujing; Huang, Youming; Xu, Danfeng; Tao, Xiaohua; Fan, Yibin (Frontiers in Public Health, 2021)
Once diagnosed, majority of patients are in their 60s and 70s and men are twice as likely to develop the BCC. However, the incidence of BCC has tripled over the last 30 years and recent years has arisen up significantly in the younger individuals and females4-6. Compared with the Western countries, the incidence of BCC in Asian population is ten to hundred folds lower, but there is also a rising tendency7-9. Although BCC rarely causes metastatic disease or death, it can result in the significant morbidity due to its destructive local spread10,11. Ultraviolet radiation (UVR) is a known carcinogen participated into the development of cutaneous cancers containing the both non-melanoma skin cancers (NMSC) and malignant melanoma (MM). Certainly, solar UVR exposure, particularly ultraviolet B (UVB), is the mostly significant environmental risk factor for the occurrence and progress of BCC. Both cumulative and intermittent high-grade UVR exposure could promote the uncontrolled replication of skin cells. Although there are other risk factors existing for skin carcinogenesis, UVR exposure has still been attributed to the development of nearly 90% of NMSC, including squamous cell carcinoma (SCC) and BCC12,13. DNA damage in formation of skin cancers is considered to be a result of UVR toxicity. It is UVR that could activate a series of oncogenes simultaneously inactivating tumor suppressor genes and aberrant proliferation and survival of keratinocytes that repair these damages. Furthermore, mounting evidence demonstrates that inflammatory responses of immune cells in the tumor microenvironment plays pivotal role in the skin tumorigenesis as well14. Therefore, changes in the environment contributing to increased UV transmission have direct implications on human health. The public should be urged to make use of the sunscreen and wear protective apparels as preventive efforts to decrease the incidence of BCC. In this chapter, we will follow the function of UVR in the onset and development of BCC. We describe the factors that influence BCC induced by UVR, and also review the recent advances of pathogenesis of BCC induced by UVR from the genetic and inflammatory aspects.